Jezik Poljanskega rokopisa - Žejn, Andrejka (Slavistična revija, 2016)
The Poljane Manuscript is believed to have been compiled around 1800 at the Capuchin monastery in Škofja Loka. Geographically, the manuscript belongs to the Rovte dialect group, which was strongly influenced by Upper Carniolan dialect innovations, and at the time of its compilation the Central Slovene standard version was in common use. The manuscript's author is unknown, but the addressee, the purpose of its creation, its relation to known models, the religious and political circumstances, and the influence of these factors on the manuscript's linguistic form can be defined. The analysis of individual phonological features shows that the author took into account both the Reformation-era written tradition and the contemporary Central Slovene standard version; in addition, many Rovte Upper Carniolan dialect features are also present that were not acceptable in the Central Slovene standard version of that time.
Keywords: 18.-19. st.; 18th-19th century; fonologija; manuscripts; phonology; Poljane manuscript; Poljanski rokopis; rokopisi; Slovene; Slovene dialects; Slovenian dialects; Slovenian language; slovenska narečja; slovenščina